Suitability of some wells water to the Human Usability at Diala Governorate (Baakoba City). Iraq (Journal of the College of Basic Education, 2022)
An analytical study of 25 wells water had been achieved as a samples choosen by the authority of wells and ground water.These wells were located at different sites scattered within Baakoba city at Diala governorate. These wells were numbered from 1 to 25 after the determination of their positions, ecology and topographic sites (The elevations above sea surface). Samples of wells water were analyzed within the months (June, July, August and September) 2010 AB. There were 19 parameters including physiochemical factors and 5 heavy metals as the following:- 1. water temperature, 2. pH, 3. E.C, 4. Turbidity, 5. Bicarbonate, 6. Sulphate, 7. Nitrate, 8. Chloride ion, 9. Ca, 10. Mg, 11. Na, 12. K, 13. Hg, 14. Pb, 15. Cu, 16. Zn, 17. Cd, 18. TDS, 19. SAR.